Sikap Peduli Lingkungan Siswa Kelas IV SD Negeri IV Sempu - Febiyana, Alva; Erviana, Lina; Nurhayati, Nurhayati (PGSD STKIP PGRI Pacitan, 2024)
This study aims to analyze: 1) the attitude of caring for the environment in of students; 2) supporting factors caring for the environment of students. This research is a qualitative research with a descriptive approach. The collecation of data used in this study is a data collaction technique of observation, interviews and documentation. The research subjects were four grade students and third . The collation techniques used were observation, interviews and documentation. Data analysis technique using data collection, techniques, data reducation, data presentation, validation and conclusions. The results of data analysis concluded that: 1) the attitude of caring for the environment in grade IV students at SD Negeri 4 Sempu showed very good results, the thing that needs to be improved is the proessing of waste into useful and creative goods. 2) The supporting factors for caring for the environment in class IV SD Negeri 4 Sempu students are self motivation, parental motivation, and teachers. Then the inhibiting factor is the frend factor around.